A new species of Constrictotermes from central Brazil with notes on the mandibular glands of workers (Isoptera: Termitidae: Nasutitermitinae) - Constantino, Reginaldo [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (My University, 1997)
Constrictotermes rupestris, new species, is described from central Brazil, with illustrations of the imago, soldier, worker head, worker mandibles, worker mandibular gland, and nest. The new species lives in a dry forest, on rocky terrain, building its nest always on rocks. In the colonies examined, all castes showed a striking reddish coloration due to something accumulated in the fat tissues. Inquilinitermes microcerus was present in most examined nests. The worker of C. rupestris has an enlarged mandibular gland. Workers also show an aggressive behavior, which suggests that the mandibular glands may produce defensive secretions.